Conditions for division and multiplication of frequencies in ferrite - Pleshev Dmitriy; Vlasov Vladimir; Asadullin Fanur; Kotov Leonid; Poleshchikov Sergey; Shavrov Vladimir; Shcheglov Vladimir (EPJ Web of Conferences, 2018)
The paper considers investigation of hypersound magnetic and elastic oscillations excitation by use of alternating magnetic field in normal magnetized plate. Distinctive features of frequency division and multiplication are studied in the paper. The relation between processes of frequency division and multiplication and structure of the plate as well as parameters of saturation magnetization, anisotropy constant, magnetic and elastic damping has been revealed.